Cannabinoid CB2 receptors are involved in the protection of RAW264.7 macrophages against the oxidative stress: an in vitro study - Sabrina Giacoppo; Agnese Gugliandolo; Oriana Trubiani; Federica Pollastro; Gianpaolo Grassi; Placido Bramanti; Emanuela Mazzon (European Journal of Histochemistry, 2017)
Research in the last decades has widely investigated the anti-oxidant properties of natural products as a therapeutic approach for the prevention and the treatment of oxidative-stress related disorders. In this context, several studies were aimed to evaluate the therapeutic potential of phytocannabinoids, the bioactive compounds of Cannabis sativa. Here, we examined the anti-oxidant ability of Cannabigerol (CBG), a non-psychotropic cannabinoid, still little known, into counteracting the hydrogen peroxide (H2O2)-induced oxidative stress in murine RAW264.7 macrophages. In addition, we tested selective receptor antagonists for cannabinoid receptors and specifically CB1R (SR141716A) and CB2R (AM630) in order to investigate through which CBG may exert its action. Taken together, our in vitro results showed that CBG is able to counteract oxidative stress by activation of CB2 receptors. CB2 antagonist pre-treatment indeed blocked the protective effects of CBG in H2O2 stimulated macrophages, while CB1R was not involved. Specifically, CBG exhibited a potent action in inhibiting oxidative stress, by down-regulation of the main oxidative markers (iNOS, nitrotyrosine and PARP-1), by preventing IκB-α phosphorylation and translocation of the nuclear factor-κB (NF-κB) and also via the modulation of MAP kinases pathway. On the other hand, CBG was found to increase anti-oxidant defense of cells by modulating superoxide dismutase-1 (SOD-1) expression and thus inhibiting cell death (results focused on balance between Bax and Bcl-2). Based on its antioxidant activities, CBG may hold great promise as an anti-oxidant agent and therefore used in clinical practice as a new approach in oxidative-stress related disorders.